Evaluation of germination and early seedling growth of different grasses irrigated with treated mine water - Mangwane, M.; Madakadze, I.C.; Nherera-Chokuda, F.V.; Dube, Sikhalazo; Mndela, M.; Letsoalo, N.; Tjelele, T.J. (MDPI, 2024)
Coal mining is known to have negative impacts on the environment, necessitating land rehabilitation after mining activities. Amongst the problems associated with coal mining is the accumulation of acid mine drainage characterized by large amounts of heavy metals and high acidity. The impact of these environmental problems on the ecosystem around mining areas underscores a need to devise strategies that will ensure sustainable restoration of the ecosystem integrity to ensure environmental protection. Of these, treatment of acid mine drainage using calcium sulfate dihydrate, which is subsequently used for irrigation during phytoremediation, holds great promise for restoration of open-cast mines. However, although grasses are used for rehabilitation of coal mined areas, the impacts of treated mine water on the germination, seedling emergence, and plant growth of grasses are not well known. The aim of the study was to evaluate the germination and early seedling growth responses of different forage grasses to treated mine water. Seven forage grass species were selected, with four species represented by two varieties while others were represented by one variety, totaling 11 forage grasses. For each plant entry, 100 seeds were placed in J.R. Petri’s dishes lined with Whatman No. 2 filter paper and watered with distilled and mine water to assess germination. For the seedling establishment experiment, only five species were studied, in which twenty seeds per species were sown in pots containing mine soil and irrigated using distilled and treated mine water. The final germination percentage (FGP), germination rate index (GRI), corrected germination rate index (CGRI), and T50 were determined for the germination trail and total biomass was assessed for the seedling growth trail. The highest FGP for all grasses was attained under controlled conditions, using distilled water, ranging from 38–94%. All grasses germinated when watered using treated mine water and had a FGP ranging from 20–91%. Relative to distilled water, GRI and CGRI were highest only for L. multiflorum cv AgriBoost when seeds were watered using the treated mine water. All grasses watered with treated mine water produced high biomass for the first two weeks, after which biomass production started to decline. Two grasses, Eragrostis curvula cv Ermelo and Lolium multiflorum cv Archie, showed tolerance to treated mine water irrespective of its high electrical conductivity (557 mS∙m−1). Therefore, these grasses could be used in the rehabilitation of coal-mined areas irrigated with treated mine water.